1990
DOI: 10.1182/blood.v75.11.2097.bloodjournal75112097
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 is a growth factor of precursor B and T acute lymphoblastic leukemia

Abstract: We investigated the proliferation-inducing effects of human recombinant interleukin-7 (IL-7) on acute lymphoblastic leukemia (ALL) cells. It is shown that IL-7 stimulates DNA synthesis in ALL cells of B-cell precursor (n = 5) as well as immature T-cell origin (n = 2). Cytogenetic analysis of the cells of four patients proliferating in IL7- supplemented cultures established the leukemic descendence of the IL-7- responsive cells. 125I-IL-7 binding experiments with the cells of one patient and with two ALL cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…7 IL-7 is present in the microenvironments where the malignant T cells arise and develop, 8 and most human primary T-cell acute lymphoblastic leukemia (T-ALL) samples express IL-7Ra 9 and proliferate in vitro in response to IL-7. [10][11][12] Accordingly, we have shown that IL-7 accelerates human T-ALL development in vivo. 13 However, the exact molecular mechanisms by which this microenvironmental factor contributes to T-ALL cell viability and proliferation remain only partially characterized.…”
Section: Introductionmentioning
confidence: 99%
“…7 IL-7 is present in the microenvironments where the malignant T cells arise and develop, 8 and most human primary T-cell acute lymphoblastic leukemia (T-ALL) samples express IL-7Ra 9 and proliferate in vitro in response to IL-7. [10][11][12] Accordingly, we have shown that IL-7 accelerates human T-ALL development in vivo. 13 However, the exact molecular mechanisms by which this microenvironmental factor contributes to T-ALL cell viability and proliferation remain only partially characterized.…”
Section: Introductionmentioning
confidence: 99%
“…No. 14 was cultured in RPMI-1640, whereas the human BM stromal line KM-102:2 a gift of Dr K. Harigaya (Chiba University, Japan), was kept in Iscove's modified Dulbecco's medium (IMDM; GIBCO; Cat. No.…”
mentioning
confidence: 99%
“…Oncogenesis IL-7/IL-7R signaling has a major impact in the survival and proliferation of T-ALL cells in vitro (e.g. Touw et al, 1990;Dibirdik et al, 1991;Barata et al, 2004a;Barata et al, 2004b) and leukemia expansion in vivo (Silva et al, 2011). Oncogenic IL7R activating mutations occur in T-ALL.…”
Section: T-cell Acute Lymphoblastic Leukemia (T-all)mentioning
confidence: 99%